Takhrij Al-Hadits: Konsep, Sejarah Perkembangan, dan Metodologi Kajian Hadis - Ahmad Kholil Al-Maghfur; Engkos Kosasih; Wahyudi Wahyudi (Yayasan Cendekia Gagayunan Indonesia, 2025)
Al-Hadith, as the second source of law after the Qur'an, encompasses many actions and sayings of the Prophet Muhammad (SAW) that serve as a model for Muslims in their daily lives. Additionally, Hadith functions to provide more detailed explanations of the laws found in the Qur'an. However, in practice, the use of Hadith often generates controversy among Muslims due to doubts regarding the authenticity, validity, and interpretation of certain Hadiths. This paper aims to examine Takhrij Al-Hadith as a method for understanding and studying Hadith, which is one of the sources of Islamic law. The method used in this research is a literature review, where the author collects information and data from various sources, such as journals, books, and articles. The findings of this study include several explanations regarding: the definition of Takhrij, the history and background of Takhrij Hadith, and the methods of Takhrij Al-Hadith based on aspects such as wording, themes, initial texts/athraf, first narrators, status/position, and the use of technology in Takhrij Hadith through Hadith CD Rooms. Furthermore, this paper also discusses the objectives and benefits of Takhrij Hadith..